2013
DOI: 10.4103/0973-1296.111287
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of Vedic Guard against doxorubicin-induced cardiotoxicity in rats: A biochemical, electrocardiographic, and histopathological study

Abstract: Background:Vedic Guard is a polyherbal formulation used in the treatment of various ailments, however, is not scientifically assessed for its effect on doxorubicin-induced cardiotoxicity.Objective:To find out the preventive role of Vedic Guard against doxorubicin-induced myocardial toxicity in rats.Materials and Methods:Cardiotoxicity was produced by doxorubicin (15 mg/kg for 2 weeks). Vedic Guard (270 mg/kg, orally) was administered as pre-treatment for 2 weeks and then for 2 weeks alternated with doxorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 16 publications
(17 reference statements)
13
20
0
Order By: Relevance
“…It suggested that the biochemical anomalies might lead to cardiotoxicity. These present observations corroborated to the earlier experimental reports (Koti et al, 2013;Mantawy et al, 2014;Matouk et al, 2013;Mukherjee et al, 2003;Singh et al, 2012). Cardiomyocytes are more susceptible to Dox-induced damage than other tissues due to highly active metabolic machinery in heart (Nohl et al, 1998;Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…It suggested that the biochemical anomalies might lead to cardiotoxicity. These present observations corroborated to the earlier experimental reports (Koti et al, 2013;Mantawy et al, 2014;Matouk et al, 2013;Mukherjee et al, 2003;Singh et al, 2012). Cardiomyocytes are more susceptible to Dox-induced damage than other tissues due to highly active metabolic machinery in heart (Nohl et al, 1998;Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…CAT, MDA, SOD and GSH-Px are important markers of oxidative stress and are widely regarded as indicators of oxidative injury [23, 24]. We measured levels of these markers to test whether pre-treatment with oxymatrine improved doxorubicin-induced metabolic derangements in rat myocardium.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Therefore, we designed the animal study to induce acute cardiotoxicity by dosing at 18 mg/kg over 10 days and evaluated the cardioprotective effect of the mRQ dosed concurrently.…”
Section: In Vivo Assessment Of Cardioprotective Effect Of Mrq In Acutmentioning
confidence: 99%